Postarthroscopy Imaging in Femoroacetabular Impingement: Persistent Pain May Be Due to an Insufficient Correction of Preoperative Abnormalities - Tudisco, Cosimo; Bisicchia, Salvatore; Tormenta, Sandro; Taglieri, Amedeo; Fanucci, Ezio (Joints, 2017)
Purpose The purpose of this study was to evaluate the effect of correction of abnormal radiographic parameters on postoperative pain in a group of patients treated arthroscopically for femoracetabular impingement (FAI).Methods A retrospective study was performed on 23 patients affected by mixed-type FAI and treated arthroscopically. There were 11 males and 12 females with a mean age of 46.5 (range: 28–67) years. Center-edge (CE) and α angles were measured on preoperative and postoperative radiographic and magnetic resonance imaging (MRI) studies and were correlated with persistent pain at follow-up.Results The mean preoperative CE and α angles were 38.6 ± 5.2 and 67.3 ± 7.2 degrees, respectively. At follow-up, in the 17 pain-free patients, the mean pre- and postoperative CE angle were 38.1 ± 5.6 and 32.6 ± 4.8 degrees, respectively, whereas the mean pre- and postoperative α angles at MRI were 66.3 ± 7.9 and 47.9 ± 8.9 degrees, respectively. In six patients with persistent hip pain, the mean pre- and postoperative CE angles were 39.8 ± 3.6 and 35.8 ± 3.1 degrees, respectively, whereas the mean pre- and postoperative α angles were 70.0 ± 3.9 and 58.8 ± 2.6 degrees, respectively. Mean values of all the analyzed radiological parameters, except CE angle in patients with pain, improved significantly after surgery. On comparing patient groups, significantly lower postoperative α angles and lower CE angle were observed in patients without pain.Conclusion In case of persistent pain after arthroscopic treatment of FAI, a new set of imaging studies must be performed because pain may be related to an insufficient correction of preoperative radiographic abnormalities.Level of Evidence Level IV, retrospective case series.
Keywords: femoroacetabular impingement; hip arthroscopy; magnetic resonance imaging; hip pain